Dietary Mineral Intake Is Associated with the Risk of Cervical Cancer: A Chinese Population-based Study (P05-037-19). (13th June 2019) - Wang, Zhe; Hao, Min; Yang, Aimin; Wang, Wenhao; Zhao, Yueyang; Su, Xiaoqiang; Liu, Yakun
Abstract: Objectives: Diet plays a significant role in the carcinogenesis. However, few studies had been conducted to evaluate the association of dietary mineral intake and risk of cervical intraepithelial neoplasia (CIN) and cervical cancer among community-based Chinese women. Methods: We performed a cross-sectional analysis of screening data in 2304 women in an ongoing cohort of 40, 000 women in China. Multivariable logistic regressions were modeled to evaluate the relationship between dietary mineral intake and CIN + risk. Results: After adjusting for multiple confounders, several dietary minerals intake were significantly associated with CIN2 + risk. Dietary calcium intake concentration was associated with the risk of CIN2 + (1st quartile versus 4th quartile: OR = 1.52, 95% CI: 1.01–2.32). The similar results were also observed for magnesium (OR = 1.80, 95% CI: 1.20–2.68), phosphorus (OR = 1.69, 95% CI: 1.12–2.55), zinc (OR = 1.55, 95% CI: 1.03–2.34) and potassium (OR = 1.92, 95% CI: 1.28–2.88). The association between dietary calcium intake and CIN1 risk (2 nd quartile compared with 4 th quartile: OR = 1.36, 95% CI: 1.03, 1.80), potassium (OR = 1.90, 95% CI: 1.27, 2.85). However, seldom statistical association was observed between other dietary mineral intake and CIN1 risk. Conclusions: Dietary nutrients such as calcium, magnesium, phosphorus, zinc, and potassium were associated with risk of CIN2+, supporting the hypothesis that dietary mineral intake play a role in the development of higher grad CIN and cervical cancer. Funding Sources: This study is supported by the Special Public Welfare Industry Research of National Health and Family Planning Commission of China (grant 201402010); This study is supported by the applied basic research project of Shanxi province (grant 201601D011086). Supporting Tables, Images and/or Graphs: